Mechanoprotection by skeletal muscle caveolae. Issue 1 (2nd January 2016) - Lo, Harriet P; Hall, Thomas E; Parton, Robert G
Abstract: Caveolae, small bulb-like pits, are the most abundant surface feature of many vertebrate cell types. The relationship of the structure of caveolae to their function has been a subject of considerable scientific interest in view of the association of caveolar dysfunction with human disease. In a recent study Lo et al. 1 investigated the organization and function of caveolae in skeletal muscle. Using quantitative 3D electron microscopy caveolae were shown to be predominantly organized into multilobed structures which provide a large reservoir of surface-connected membrane underlying the sarcolemma. These structures were preferentially disassembled in response to changes in membrane tension. Perturbation or loss of caveolae in mouse and zebrafish models suggested that caveolae can protect the muscle sarcolemma against damage in response to excessive membrane activity. Flattening of caveolae to release membrane into the bulk plasma membrane in response to increased membrane tension can allow cell shape changes and prevent membrane rupture. In addition, disassembly of caveolae can have widespread effects on lipid-based plasma membrane organization. These findings suggest that the ability of the caveolar membrane system to respond to mechanical forces is a crucial evolutionarily-conserved process which is compromised in disease conditions associated with mutations in key caveolar components.